Estudo comparativo dos escalonadores de pacotes que geram QoS em uma rede de dados - Barbosa, Danúbia Ravena Silva (2011)
This work intends to present a comparative study of packages schedulers that generate quality of service (QoS) in a data network, the same quality specifications has generated within the network where data is managed and the packet stream from traffic which uses a set of scheduling mechanisms. The QoS architecture is seeking to ensure quality services and traffic in computer networks. Traffic control is the set of mechanisms that come through escalation of packets within a router. Routers are central to obtaining the necessary quality in the packets that travel over the network through to reach their final destination.